Antibiotics in water and sediments from Liao River in Jilin Province, China: occurrence, distribution, and risk assessment - Dong, Deming; Zhang, Liwen; Liu, Shuang; Guo, Zhiyong; Hua, Xiuyi (Environmental earth sciences, 2016)
The seasonal and spatial variations of 12 selected antibiotics belonging to four groups, including sulfonamides, quinolones, tetracyclines, and macrolides, were investigated in three main tributaries of Liao River in Jilin Province, northeast China. The concentrations of the antibiotics in the surface water and surface sediments were determined by HPLC–MS/MS. The results indicated that oxytetracycline (OTC), erythromycin (ETM), and ofloxacin (OFL) were dominant antibiotics in the water, with mean concentration of 174.9 ± 266.9, 103.2 ± 95.5, and 67.1 ± 77.3 ng/L, respectively, while OFL, OTC, and norfloxacin were prominent antibiotics in sediments, with mean concentration of 152.2 ± 108.3, 149.5 ± 147.6, and 62.8 ± 83.3 ng/g, respectively. The total antibiotic concentrations in water at each sampling site were 1.2–3 times higher in autumn (November 2015) than those in summer (July 2015), whereas antibiotic concentrations in sediments showed no significant seasonal variation. The highest total antibiotic concentrations in water and sediments were observed around cities with large populations of humans and livestock. Risk assessment based on single antibiotic exposure revealed that OFL, ETM, and OTC were main antibiotics with potential adverse ecological consequences for aquatic organisms. In addition, the mixtures of selected antibiotics posed medium to high risk for aquatic organisms in the Liao River in Jilin Province.